Impact of the customs union of Belarus, Kazakstan and Russia on the trade policy of Kazakhstan - KUSSALIYEVA, Aigul (KDI School, 2015)
This study analyses the pattern of trade flows/specialization from Kazakhstan to the Customs Union member countries and rest of the world. Our research is mainly based on different measures of trade indexes in addition to the analysis of product composition and trade destinations of Kazakhstani exports. The present work also aims to explain the impact of joining the Customs Union on trade policy of Kazakhstan and suggests related policy recommendations on that.
Thesis(Master) --KDI School:Master of Public Policy,2015